Sarcófagos paleocristianos en Murcia y zonas limítrofes - Sotomayor, Manuel (Antigüedad y Cristianismo, 1998)
Here are collected and studied the fragments of Sarcophagi found at different times in Begastri (Cehegín, Murcia), Yecla (Murcia), Elda (Alicante) and Hellín (Albacete), all places near one another. Al1 these constitute an important body of documents about the christianisation of the region. Al1 the fragments came from Rome and testify to the faith and economic power of the owners; some of the sarcophagi show signs of successive use in later centuries. The peculiarities of the iconography are also described. (...)